Upaya peningkatan kadar lengas dan permeabilitas tanah alfisol menggunakan bahan organik dan jamur mikoriza arbuskula sebagai medium tanaman jagung - Zulkoni, Akhsin (UNIVERSITAS PEMBANGUNAN NASIONAL â€VETERANâ€ YOGYAKARTA, 2014)
Maize (Zea mays, L.) is one type of plant included in family Graminaceae. The fibrous roots require soil nests so that it becomes easier for root penetration. Benefits of organic material and Vesicular-Arbuscular-Mycorrhizae (VAM)on the growth of maize obtained through its influence on improvement of soil physical properties. The study of efforts to increase moisture levels and permeability of soil organic matter on Alfisol soil using VAM aims to find the best formula between the dose of organic material and the VAM inoculation to improve Alfisol physical properties. Experiment arranged in a randomized complete block design with three replications. The first factor was a dose of organic manures, including 0 tons ha-1 (B0), 20 tons ha-1 (B1), 40 t ha-1 (B2), and 60 tons ha-1 (B3). The second factor was inoculation VAM, which were no inoculation (J0) and with VAM inoculation (J1). Soil moisture level was analyzed using Gravimetri methods and soil permeability was analyzed using a permeameter. The data subjected to analysis of variance followed by LeastSignificant Difference (Î±: 5%).The results showed that the application of organic manures 40 tons ha-1 in combination with inoculation VAM is the best treatment for improving soil physical properties. Soil moisture levels reached 15.72%, increased 7.32% from the control levels of 8.40%. Similarly, permeability land rose from 0.51 cm s-1 to 1.38 cm s-1. Provision of organic matter and inoculation VAM cause for the better soil structure, increasing water holding capacity, and the ability of the soil to pass water easily.Jagung (Zea mays, L.) adalah salah satu jenis tanaman bii-bijian dari keluarga Graminaceae yang berakar serabut sehingga memerlukan tanah yang sarang agar penetrasi akar menjadi lebih mudah. Manfaat bahan organik dan Jamur Mikoriza Arbuskula (JMA) terhadap pertumbuhan jagung diperoleh melalui pengaruhnya terhadap perbaikan sifat fisika,tanah. Kajian mengenai upaya peningkatan kadar lengas dan permeabilitas tanah Alfisol menggunakan bahan organik dan JMA bertujuan untuk mencari formula terbaik antara takaran bahan organik dan inoklasi JMA terhadap perbaikan sifat fisika Alfisol. Percobaan disusun dalam rancangan faktorial secara acak kelompok lengkap, dengan tiga ulangan. Fakor pertama adalah takaran bahan organik, meliputi 0 ton ha-1 (B0), 20 ton ha-1 (B1), 40 ton ha-1 (B2), dan 60 ton ha-1 (B3). Faktor kedua adalah inokulasi JMA, yaitu tidak dilakukan inokulasi (J0) dan dilakukan inokulasi (J1). Parameter yang dianalisis yakni kadar lengas tanah keringangin menggunakan metoda Gravinetri dan permeabilitas tanah menggunakan alat permeameter